Treatment of cerebral radiation necrosis with nerve growth factor: A prospective, randomized, controlled phase II study. Issue 1 (July 2016) - Wang, Xiao Shen; Ying, Hong Mei; He, Xia Yun; Zhou, Zheng Rong; Wu, Yong Ru; Hu, Chao Su
Abstract: Purpose: A prospective, placebo controlled phase II trial was conducted to test the efficacy of Nerve Growth Factor (NGF) for the treatment of symptomatic temporal lobe necrosis (TLN). Materials and methods: Patients with progressive TLN were randomly assigned to either the control or the study group in a 1:1 ratio. The control group received corticosteroids with gradually reduced dosage. The study group received NGF with corticosteroids. NGF was dissolved in 2 mL normal saline and injected intramuscularly at 18 μg/time, once a day for 2 months. The efficacy was evaluated by both the objective and subjective methods every 3–4 months after treatment. The objective method compared volumes of the necrotic masses on MRI before and after treatment. The subjective method compared the neurocognitive score as evaluated by the mini–mental status examination (MMSE). Results: Twenty-eight cases were enrolled into this study. The objective evaluation showed that the response rate (RR) in the study group was higher than the control group. The ratio was 10 versus 2 ( p = 0.006), and 12 versus 3 ( p = 0.002) at 3–4 months and 6–8 months after intervention, respectively. The subjective evaluation demonstrated both groups were effective in controlling the necrosis related symptoms in the first 6 months after treatment. But NGF was more effective than corticosteroids at 9 months (13 versus 4, p = 0.001). The only observed side effect was mild pain at the injection site in 3 patients in the study group. Conclusions: Our results demonstrated that the process of TLN is not irreversible. NGF is more effective in recovering TLN than corticosteroids with little side effect. NGF has a longer duration in controlling the necrosis related symptoms than corticosteroids.